The Value of Using the Reaction of Indirect Hemagglutination in Coenurosis - Kilichevich, Gaznakulov Tojimurod; Abdurahmonovna, Kilicheva Madina (Research Parks Publishing LLC, 2023)
The paper presents a laboratory method for diagnosing coenurosis, known in the worl Summary The paper presents a laboratory method for diagnosing coenurosis, known in the world.